Peningkatan Kualitas Papan Komposit Limbah Batang Kelapa Sawit (Elaeis guineensis Jacq.) Dengan Berbagai Water Repellent - M. Hakim Muslim; Luthfi Hakim; Yunus Afifuddin (Peronema Forestry Science Journal, 2013)
Ever-increasing demand for wood and forest potential of shrinking demand the use of wood in an efficient and prudent, for example by utilizing waste oil palm trunks which have not been optimally utilized a high-quality products for the future. The purpose of this study was to test the stability and strength of composite boards from waste oil palm trunks with a ratio of water-resistant coating acrylic of various brands. The hypothesis of this study is the differences between different brands of acrylic that affect the physical properties and mechanical properties of composite boards from oil palm trunk waste. There are three treatments in this study, which refers to the first treatment of the outer coating of the composite board with a water repellent Aquaproof brand, treatment of both the outer coating with MultiGuard composite board, and the third with a Waterproof coating. Testing of physical properties and mechanical properties refer to JIS A 5908-2003. The results showed that physical properties of the density has reached the target density with a value of 0.8 gr/cm3, where the density range of 0.78 - 0.82 gr/cm3, water content ranged from 8:23 to 9:11%, water absorption ranged from 8.69 - 10.86%, the development of thick for 2 hours ranged between 3.1 - 4.92% and thickness development during the 24 hours range from 11:34 to 15:53​​%. Meanwhile, for the results of testing the mechanical properties of obtained results of an internal bond 8:19 ​​- 10.81 kg/cm2, a strong grasp of the screw 56.29 - 59.55 kgf, MOE 21124.08 - 31852.83 kg/cm2 and MOR reached 279.62 - 378.36 kg/cm2. Keywords: palm wood, composite boards, isocyanate, acrylic, and water repellent.